Inhibition of mmu_circ_0009303 improves metabolic dysfunction-associated steatotic liver disease by regulating lipid metabolism and oxidative stress - Ju Zhou; Wu Li; Xiaowei Chi; Dingchun Li; Chunxia Yang; Zhiwen Duan (Endocrine Journal)
Circular RNAs (circRNAs) play an important role in regulating inflammation and oxidative stress during the pathogenesis of metabolic dysfunction-associated steatotic liver disease (MASLD); however, the underlying mechanism is unclear. This study aimed to determine the role of mmu_circ_0009303 in MASLD. We used a bioinformatics approach to identify potential targets and established an in vitro model of MASLD. Oil red O staining, cell transfection and dual-luciferase reporter assay were used to determine the role of mmu_circ_0009303. The results indicated that the mmu_circ_0009303 expression was significantly increased in the MASLD model both in vitro and in vivo and was associated with oxidative stress levels and inflammation. Moreover, bioinformatics analyses revealed that miRNA-182-5p and Foxo3 are targets of mmu_circ_0009303 and miRNA-182-5p, respectively. In the in vitro MASLD model, mmu_circ_0009303 promoted fat deposition in NCTC1469 cells, which was induced by free fatty acid (FFA) through the regulation of miRNA-182-5p/Foxo3. The expression of miRNA-182-5p and Forkhead box O3 (Foxo3) was associated with mmu_circ_0009303 expression in the liver of mice with MASLD, which was induced by a high-fat diet. Furthermore, mmu_circ_0009303 may be involved in regulating the expression of lipid metabolism-related regulatory proteins, such as CPT1A, SLC27A4, ACBD3, SREBP1, FAS, PPARα, and PPARγ. Taken together, mmu_circ_0009303 promotes oxidative stress, inflammation, and excessive fat accumulation in NCTC1469 cells induced by FFA through the regulation of miRNA-182-5p/Foxo3 and lipid metabolism-related regulatory proteins. These findings provide a potential target for the treatment of MASLD.